Patellar tendon ossification after retrograde intramedullary nailing for distal femoral shaft fracture: A case report and review of the literature. Issue 47 (November 2017) - Tan, Lei; Wang, Tiejun; Li, Yan-Hui; Yang, Tianye; Hao, Baohui; Zhu, Dong; Sun, Da-Hui
Abstract: Rationale: Retrograde femoral nailing was one of the most important treatment means for distal femoral shaft fracture. However, studies regarding heterotopic ossification of the patellar tendon after retrograde intramedullary nailing for distal femoral shaft fracture are limited. We herein present a rare complication, namely heterotopic ossification of the patellar tendon, after retrograde intramedullary nailing for displaced femoral shaft fracture. Patient concerns: We present a case of 25-year-old male with displaced femoral shaft fracture who was treated by retrograde intramedullary nailing. Diagnoses: During the period of follow-up, the patient developed symptomatic heterotopic ossification of the patellar tendon with extensively hard ossification area. Interventions: Open surgery was recommended, but the patient has refused further treatment. Outcomes: The patient resulted in pain and restricted the range of motion of the affected knee. Lessons: This case stresses the importance of longer-term follow-up and further attention into the possibility of heterotopic ossification of the patellar tendon.